Health Benefits of Different Sports : a Systematic Review and Meta-Analysis of Longitudinal and Intervention Studies Including 2.6 Million Adult Participants - Oja, Pekka (Springer Nature, 2025)
Background Several reviews have examined the health benefits of participation in specific sports, such as baseball, cricket, cross-country skiing, cycling, downhill skiing, football, golf, judo, rugby, running and swimming. However, new primary studies on the topic have recently been published, and the respective meta-analytic evidence needs to be updated.
Objectives To systematically review, summarise and appraise evidence on physical health benefits of participation in different recreational sports.
Methods Searches for journal articles were conducted in PubMed/MEDLINE, Scopus, SpoLit, SPORTDiscus, Sports Medicine & Education Index and Web of Science. We included longitudinal and intervention studies investigating physical health outcomes associated with participation in a given sport among generally healthy adults without disability.
Results A total of 136 papers from 76 studies conducted among 2.6 million participants were included in the review. Our meta-analyses of available evidence found that: (1) cycling reduces the risk of coronary heart disease by 16% (pooled hazard ratio [HR] = 0.84; 95% confidence interval [CI]: 0.80, 0.89), all-cause mortality by 21% (HR = 0.79; 95% CI: 0.73, 0.84), cancer mortality by 10% (HR = 0.90; 95% CI: 0.85, 0.96) and cardiovascular mortality by 20% (HR = 0.80; 95% CI: 0.74, 0.86); (2) football has favourable effects on body composition, blood lipids, fasting blood glucose, blood pressure, cardiovascular function at rest, cardiorespiratory fitness and bone strength (p < 0.050); (3) handball has favourable effects on body composition and cardiorespiratory fitness (p < 0.050); (4) running reduces the risk of all-cause mortality by 23% (HR = 0.77; 95% CI: 0.70, 0.85), cancer mortality by 20% (HR = 0.80; 95% CI: 0.72, 0.89) and cardiovascular mortality by 27% (HR = 0.73; 95% CI: 0.57, 0.94) and improves body composition, cardiovascular function at rest and cardiorespiratory fitness (p < 0.010); and (5) swimming reduces the risk of all-cause mortality by 24% (HR = 0.76; 95% CI: 0.63, 0.92) and improves body composition and blood lipids (p < 0.010).
Conclusions A range of physical health benefits are associated with participation in recreational cycling, football, handball, running and swimming. More studies are needed to enable meta-analyses of health benefits of participation in other sports. PROSPERO registration number CRD42021234839.